Traveling Companions: Monthly Review and Latin America - Ortega, Jaime (Meridional. Revista Chilena de Estudios Latinoamericanos, 2020)
Magazines with a political orientation have become a source for understanding intellectual history, they continent as much the development of certain ideologies as the networks built over time and space. With the enlightened spirit that distinguishes it, the Marxist left found in these publications a means to understand its reality and also to intervene in it. Intellectual intervention exceeded its immediate frameworks of action and projected knowledge about other realities, while accumulating specific knowledge about certain geographic areas. In this work, the place occupied by Latin American societies will be outlined in a recognized magazine of the United States: Monthly Review. This will allow us to understand the main anchor points, debates and authors that circulated through its pages